"The impact of World War II on modern Europe" (Comprehensive Journal of Science, 2025)
economic, and social transformations that reshaped the continent after 1945. The war led to the collapse of much of Europe’s infrastructure and the weakening of traditional political powers, paving the way for a new international order based on bipolarity between the United States and the Soviet Union. It also redrew Europe’s political map, dividing it into Eastern and Western blocs, while reconstruction programs such as the Marshall Plan played a crucial role in economic recovery. Socially and culturally, the war brought significant demographic changes and shifts in societal values, contributing to the emergence of concepts such as the welfare state, human rights, and European integration. The study concludes that World War II was a decisive turning point in shaping modern Europe.
Keywords: World War II, Modern Europe, Reconstruction, Bipolar System, Marshall Plan, European Integration, Cold War.